Efektivitas Penerapan Whistleblowing System (Studi pada 4 Bank BUMN Terbesar di Indonesia Periode 2019 – 2022) - Maharani, I Gusti Ayu Angelica Tara Phoebe; Sudarma, Made (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2024)
This study aims to analyze the effectiveness of whistleblowing system in preventing violation cases on 4 Largest State-Owned Banks in Indonesia between 2019 and 2022. This study employs descriptive qualitative approach, involving secondary data of the companies' Annual Report containing data on violation reporting through the whistleblowing system mechanism. The data are collected from a literature study by conducting qualitative content analysis. The results and discussion of this study exhibit that the Whistleblowing System implementations of PT. Bank Rakyat Indonesia (Persero) Tbk and PT. Bank Tabungan Negara (Persero) Tbk. have been effective in detecting and preventing fraud, different from those of PT. Bank Negara Indonesia (Persero) Tbk and PT. Bank Mandiri (Persero) Tbk which are still less effective in detecting and preventing fraud.